Answer:
F
for A > F
for B
Hence, Bearing A can carry the larger load
Step-by-step explanation:
Given the data in the question,
First lets consider an application which requires desired speed of n₀ and a desired life of L₀.
Lets start with Bearing A
so we write the relation between desired load and life catalog load and life;
=
![F_D(L_Dn_D60)^(1/a)](https://img.qammunity.org/2022/formulas/engineering/college/oiczcdfrycw9x1xa0k2i2q68heqgx74asx.png)
where F
is the catalog rating( 2.12 kN)
L
is the rating life ( 3000 hours )
n
is the rating speed ( 500 rev/min )
F
is the desired load
L
is the desired life ( L₀ )
n
is the the desired speed ( n₀ )
Now as we know, a = 3 for ball bearings
so we substitute
=
950.0578 =
950.0578 / 3.914867 =
![F_D( L_0n_0)^(1/3)](https://img.qammunity.org/2022/formulas/engineering/college/9hksv133ezq3papvhxyuifjgpviu4oj20s.png)
242.6794 =
![F_D( L_0n_0)^(1/3)](https://img.qammunity.org/2022/formulas/engineering/college/9hksv133ezq3papvhxyuifjgpviu4oj20s.png)
F
for A = (242.6794 /
) kN
Therefore the load that bearing A can carry is (242.6794 /
) kN
Next is Bearing B
=
![F_D(L_Dn_D60)^(1/a)](https://img.qammunity.org/2022/formulas/engineering/college/oiczcdfrycw9x1xa0k2i2q68heqgx74asx.png)
F
= 7.5 kN,
![(L_Rn_R60) = 10^6](https://img.qammunity.org/2022/formulas/engineering/college/dc7kwiwtgja6yd2dec6whgo8asb9uv1zkh.png)
Also, for ball bearings, a = 3
so we substitute
=
![F_D(L_0n_060)^(1/3)](https://img.qammunity.org/2022/formulas/engineering/college/rpcon1lsjc40byvz9nsis2jgg53wwc4isa.png)
750 =
![F_D(L_0n_0)^(1/3) 3.914867](https://img.qammunity.org/2022/formulas/engineering/college/6rwvqpvhzimvvcyaz459ctmar4n1kzztml.png)
750 / 3.914867 =
![F_D(L_0n_0)^(1/3)](https://img.qammunity.org/2022/formulas/engineering/college/wuamwuw0lni5zp3bc9svb4itrzs574jo7r.png)
191.5773 =
![F_D(L_0n_0)^(1/3)](https://img.qammunity.org/2022/formulas/engineering/college/wuamwuw0lni5zp3bc9svb4itrzs574jo7r.png)
F
for B = ( 191.5773 /
) kN
Therefore, the load that bearing B can carry is ( 191.5773 /
) kN
Now, comparing the Two results above,
we can say;
F
for A > F
for B
Hence, Bearing A can carry the larger load